Dual‐passivity‐based control strategy of modular multilevel matrix converter. (12th November 2020) - Ma, Xinqiao; Cheng, Qiming; Cheng, Yinman; Rui, Xinhua; Zhao, Juefei
Summary: Complying with the trend of renewable energy power generation, the Modular Multilevel Matrix Converter (MMMC, also known as M3C) is applied to the low‐frequency alternating current (AC) transmission system to realize the AC/AC conversion from low‐frequency AC to power‐frequency AC based on the offshore wind power generation. In view of the shortcomings of traditional proportional integral (PI) control, such as slow response, more adjustment parameters and low dynamic performance, a new type of nonlinear control based on passive theory is proposed in this paper, namely passivity‐based control. It has the advantages of fast response, less adjustment parameters, and high dynamic performance, which can greatly improve the control effects of the M3C input and output sides current. Under operating conditions such as input‐side frequency changes and output power changes, the passivity‐based control strategy can still maintain a very low system impact, and the overall control effect is better. Finally, the correctness and superiority of this method are verified by simulation under different working conditions. Abstract : The figure above shows the overall control block diagram of M3C. As can be seen from the figure, the control system of M3C is mainly composed of input‐side, cluster voltage and circulating current, output‐side, common mode voltage, and the sub‐module of the H‐bridge. Among them: (1) The input‐side control is mainly by collecting the u m x and i m x of the M3C input‐side port, after the dq transformation, we can get the traditional control method of input‐side, that is, PI control (see Section 3.1.1 for details). In this paper, the passiveness of the mathematical model on the input‐side is analyzed, and the passivity‐based control based on the Euler‐Lagrange model is designed according to the passive theory. For the detailed theoretical analysis and derivation process, see Section 3.1.2. (2) The control of the cluster voltage and the circulating current is realized by setting up the power‐capacitance voltage model of M3C. After the transformation of double αβ 0, by designing the circulating current to adjust the possible DC drift, and then realize the circulating current control. The control block diagram is shown in Figure 5. (3) The output‐side control and the input‐side control are similar. (4) The common mode voltage control is to maintain the balance of the cluster voltage by injecting the common mode voltage u nN . The method of designing circulating current has been adopted in the article, so it is not necessary to consider injecting the common mode voltage, that is, u nN = 0. (5) The voltage equalization control of the H bridge sub‐module is achieved by collecting the cluster current i xy, the cluster voltage u xy and the capacitance voltage u c xyi of the i th H bridge sub‐module on the xy cluster. And then combining the control of the input‐side, the clusters and the output‐side, we can get the equalizing control law of the H‐bridge sub‐module. The control block diagram is shown in Figure 6.